Nursing performance in mental health: An integrative literature review (Research, Society and Development, 2025)
Introduction: Nursing plays a fundamental role in the context of mental health care, since it acts directly in the care of patients with mental disorders. Objective: to present nursing care in the field of mental health, focusing on practices, challenges and contributions to the promotion of psychosocial well-being of patients according to the literature. Methodology: integrative literature review. The SciELO, LILACS, BDENF and PubMed databases were used as a search source, from articles published in the years 2020 to 2025, in Portuguese, Spanish and English, using the descriptors: psychiatric nursing, mental health, humanization of care and nursing interventions. The research was prepared seeking to answer the guiding question: "what have been the main challenges and contributions of Nursing in the field of mental health?" Results: given the findings, the importance of nursing in mental health was evidenced, as well as the challenges faced and the strategies to optimize care. The implementation of humanized practices, continuous professional qualification and the strengthening of the care network were identified as fundamental to improve the care offered to patients. Conclusion: overcoming structural challenges and empowering professionals are essential actions suggested to ensure efficient and accessible care, contributing to the improvement of mental health in society.